2015
DOI: 10.1016/j.pharep.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Dezocine prevents sufentanil-induced cough during general anesthesia induction: A randomized controlled trial

Abstract: The results of current study suggest that administration of Dezocine 0.1mg/kg may effectively prevent the occurrence and reflex degree of sufentanil-induced irritating cough in general anesthesia induction in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 13 publications
1
76
0
Order By: Relevance
“…Our previous study proposed that the dezocine-mediated suppression of the cough induced by sufentanil may be mainly associated with κ-receptor antagonism, which in turn antagonizes sufentanil-activated μ receptors, thereby reducing cough. 15 Nalbuphine is a synthetic opioid (μ-receptor antagonist and κ-receptor agonist), and the common use dose ranges from 0.2 mg/kg to 0.4 mg/kg. 16 The onset time of nalbuphine was 2-3 minutes, 17 so in our study, the pretreatment drug was administered at 150 s before sufentanil injection.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study proposed that the dezocine-mediated suppression of the cough induced by sufentanil may be mainly associated with κ-receptor antagonism, which in turn antagonizes sufentanil-activated μ receptors, thereby reducing cough. 15 Nalbuphine is a synthetic opioid (μ-receptor antagonist and κ-receptor agonist), and the common use dose ranges from 0.2 mg/kg to 0.4 mg/kg. 16 The onset time of nalbuphine was 2-3 minutes, 17 so in our study, the pretreatment drug was administered at 150 s before sufentanil injection.…”
Section: Discussionmentioning
confidence: 99%
“… 27 28 Induced cough can be reduced by propofol 29 and interestingly, by another opioid, dezocine. 30 Dezocine is an opioid analgesic acting on μ-, δ- and κ-opioid receptors and has been used in propofol sedation. 31–33 Oxycodone is an opioid alkaloid acting on μ- and κ-opioid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is commonly accompanied with opioid-induced cough, respiratory depression, and postoperative nausea and vomiting during induction of general anesthesia [1]. Previous studies have found that the incidence of fentanyl-induced cough varies between 2.7% and 65% [2,3]. The tussive effect of sufentanil is usually transient and self-limited for most patients.…”
Section: Introductionmentioning
confidence: 99%